Establishment and effect evaluation of an aortic dissection model induced by different doses of β-aminopropionitrile in rats. (December 2021) - Lv, Xiaochai; Hu, Yunnan; Chen, Xiaodong; Chen, Xingfeng; Chen, Liangwan; Lin, Yong; Hou, Yanting
Introduction: Given the controversy regarding the appropriate dose of β-aminopropionitrile for induction of aortic dissection models in rats, the purpose of this study was to explore the most suitable concentration of β-aminopropionitrile to establish a high-incidence and low-mortality aortic dissection model. Methods: Eighty three-week-old male Sprague-Dawley rats were equally divided into four groups: a control group, a 0.06% β-aminopropionitrile group, a 0.08% β-aminopropionitrile group and a 0.1% β-aminopropionitrile group. Initial experiments were performed on the control group, which was not treated with β-aminopropionitrile (and drank water freely), and the other three groups, which were given different concentrations of β-aminopropionitrile solution daily (0.06%, 0.08% and 0.1%). Subsequently, on the 40th day, osmotic minipumps administering 1 μg/kg per min angiotensin II (Ang II) were implanted subcutaneously into the β-aminopropionitrile groups, while the control group was continuously pumped with normal saline. The rats were euthanized 48 h after implantation. All rats that died before the expected end time of the experiment were autopsied immediately, and the aortas were dissected. The rats surviving at the end of the experiment were sacrificed by an overdose of sodium pentobarbital, and tissue samples were harvested for further analyses. Results: The mean survival days were significantly different among the groups, with 39.1 ± 6.04 days in the 0.08% β-aminopropionitrile group and 32.7 ± 9.85 days in the 0.1% β-aminopropionitrile group ( P  = 0.0178) at the end of the experiment. Compared with those in the 0.06% β-aminopropionitrile group, the rates of aortic dissection were significantly higher in the 0.08% β-aminopropionitrile group and the 0.1% β-aminopropionitrile group ( P  = 0.0015 and P  = 0.0005, respectively), while there was no significant difference between the 0.08% β-aminopropionitrile group and the 0.1% β-aminopropionitrile group ( P  = 0.723) at 70% and 75%, respectively. However, the rupture rates were significantly different between the 0.08% β-aminopropionitrile group and the 0.1% β-aminopropionitrile group (55% versus 20%, P  = 0.022). Hematoxylin-eosin staining of the aortic tissue sections of the β-aminopropionitrile group showed that red blood cells entered the pseudocavity in the vascular wall, while the vascular wall structure of the control group was intact. Compared with control rats, which were intact and free from fracture, β-aminopropionitrile-treated rats had fewer collagen fibers and exhibited fracture. Magnetic resonance imaging showed that the aortic intimae of the aortic dissection rats showed double lumens and intimal tears. Conclusions: An aortic dissection model with a high incidence and low mortality was successfully and stably developed with 0.08% β-aminopropionitrile. This model will enable further studies investigating aortic dissection pathogenesis and drug therapy. Magnetic resonance imaging may be a reliable technique for imaging the aorta in rats.